Development of scale for assessing farmers' attitude towards precision conservation agricultural practices - A, SHITU G; NAIN, M S; KOBBA, FREDERICK (The Indian Journal of Agricultural Sciences, 2023)
Attitude is a behavioural construct that cannot be measured by a single variable, hence the need for developing a standardized instrument for its measurement. The present study has been conducted to develop a reliable and valid instrument for exploration of farmers’ attitudinal orientation towards Precision Conservation Agricultural Practices (PCAPs). PCAPs are technologies and practices that are capable of helping farmers to apply right resources at the right place, at the right time, with a right method. The combination of these technologies and practices can help in achieving optimum resource stewardship and resource conservation at the farmers’ field. However, the attitude of farmers’ may influence the uptake of these practices at farmers’ field. A step by step procedure of developing standardized attitude scale was followed using Likert’s summated rating approach. The steps include item collection, relevancy test, item analysis, reliability test as well as validity test. Finally, thirty items were selected for the attitude scale which were found reliable at Spearman Brown coefficient of 0.75 and satisfied content validity. The attitude scale may be useful for researchers and extension functionaries in the field of Precision Conservation Agriculture (PCA) as well as climate smart agriculture (CSA).